PENGARUH TRAIT KEPRIBADIAN TERHADAP GAYA HIDUP HEDONISME PRAMUGARI MASKAPAI â€œLA - Handayani, Andi; Wijaya, Yeni Duriana (Jurnal Psikologi, 2016)
AbstractFlight attendant profession demands to look beautiful and attractive, directs them to do hedonism lifestyle. As well as,flight attendant as its brand company image its one of the reason they do hedonism lifestyle, and they do in different ways. One of the factors that influence hedonism lifestyle is a personality trait which have by each people.The purpose of this study is to see representative of a personality trait determine the influence of personality traits with hedonism life style and hedonistic life style differences based on trait personality. The design of this study is a quantitative with probability sampling and simple random sampling evidence. Total sample in this research is 328 flight attendants PT. LA. The coefficient of reliability of the measuring instrument trait of personality(Î±) =0.937 and measuring the hedonism lifestyle (Î±) =Î±.0,847.Z-score result personality dominan is a trait conscientiousness, ANOVA test results of the personality trait of the hedonistic life style that the value sig(p) =.000(p <0.05) means that there isa significant influence on the personality trait hedonistic lifestyle. Further more,based on the results of the ANOVA posthoctest result hedonistic lifestyle differences in trait personality trait conscientiousness and neuroticism have significant differences compared to the other trait.Keywords: traits personality, lifestyle hedonism, flight attendantsÂ AbstrakTuntutan profesi pramugari untuk selalu tampil cantik dan menarik serta menjaga image perusahaan mengarahkan mereka pada gaya hidup hedonisme. Pramugari memiliki perbedaan cara dalam melakukan aktivitas gaya hidup hedonisme. Salah satu fakor yang mempengaruhinya adalah trait kepribadian yang dimiliki oleh setiap pramugari. Tujuan dari penelitian ini untuk melihat gambaran trait kepribadian pramugari, mengetahui pengaruh trait kepribadian terhadap gaya hidup hedonisme pramugari maskapai LA dan perbedaan gaya hidup hedonisme berdasarkan trait kepribadian. Rancangan penelitian ini adalah kuantitatif dengan teknik probability sampling dan jenis simple random sampling, berjumlah328 pramugari LA. Koefisien reliabilitas dari alat ukur trait kepribadian yaitu (Î±)= 0,937 dan gaya hidup ( Î± ) = 0,847. Hasil uji Zscore, trait conscient paling dominan dengan frekuensi 81,dan pada uji anova trait kepribadian terhadap gaya hidup hedonisme diperoleh nilai sig (p)=.000 (p<0.05) Artinya terdapat pengaruh signifikan trait kepribadian terhadap gaya hidup hedonisme. Selanjutnya berdasarkan hasil uji post hoc pada Anova diperoleh hasil perbedaan yang significant gaya hidup hedonisme pada trait kepribadian conscientiousness dan neurotisme.Kata kunci: trait kepribadian, gaya hidup hedonisme, pramugari